Impacts of Quality Design BIM Towards the Malaysian Construction Industry - Tan, Zhi Cong; YAHYA, MOHD YAMANI (Research in Management of Technology and Business, 2024)
Building Information Modelling (BIM) is the recent technology in the construction industry and makes impact towards building quality design. BIM helps the construction industry to manage design quality all through the construction project tends to boost buildings performance by ensuring that all phases of the project meet the customer's criteria and are secure for consumers. The traditional construction industry had faced challenges in quality design like drawing 2D plan by hand, it costs a lot of time to complete. Thus, the objectives were to determine the challenges before using BIM technology on quality design for construction industry and impact of after using BIM technology on quality design, and implementation strategies of BIM in quality design. The qualitative research used in this study, which is semi-structural interview had been conducted with architect that had experience used BIM in construction project in Johor Bahru area. The data had been collected and transferred to transcribe; the content analysis matrix table was using to analyse the data The research findings and the results had meet with the three objectives of the study which is drawing skill with hand sketching is the main challenges before using BIM technology on quality design, BIM produce better model quality and improve quality and lifespan of building are the main impact of after using BIM technology for quality design. The implementation strategies for BIM in quality design also indicated by respondent which is employing competent staff to operate BIM software.